Workshop Pengembangan Media Pembelajaran Interaktif Kimia menggunakan Canva dan ChatGPT - Gani, Abdul (Lembaga Yasin AlSys, 2025)
The integration of digital technology into 21st-century chemistry education is driving a transformation toward more contextual, interactive, and student-centered learning approaches. This study aims to evaluate the impact of structured training on improving teachers’ abilities to design interactive chemistry learning media using Canva and ChatGPT. A quantitative method was employed with a one-group pretest–posttest pre-experimental design, involving 15 chemistry teachers from three Madrasah Aliyah in Central Lombok. The training consisted of hands-on sessions focused on using Canva for visual design and ChatGPT for content development, guided by the Technological Pedagogical Content Knowledge (TPACK) framework and the Digital Competence Framework for Educators (DigCompEdu). The results revealed a significant improvement in teachers’ design skills, indicated by an increase in the average score from 58.40 (pretest) to 81.73 (posttest), which was statistically significant according to the paired sample t-test (t = 7.452, p < 0.05). Additionally, participants expressed highly positive perceptions of the training, particularly regarding its relevance, applicability, and contribution to professional development. These findings affirm the effectiveness of integrating digital design platforms and artificial intelligence in enhancing the quality of chemistry instruction. The study underscores the importance of continuous professional development programs to foster technology-based innovative pedagogy.